Application of The Balanced Scorecard as a Benchmark For Performance Assessment at the Surya Abadi Situbondo Multi Business Cooperative - Norma Ilviatus Suhro; Diana Dwi Astuti; Lia Rachmawati (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
This research aims to determine the performance of the Surya Abadi Cooperative when measured using a financial perspective, customer perspective, internal business process perspective, learning and growth perspective. This research uses a purposive sampling method, which means researchers tend to choose informants who are considered to know the information and problems in depth and can be trusted. The results of this research found that based on the conclusions from each perspective of the Balanced Scorecard, it can be concluded that overall KSU Surya Abadi Situbondo has quite good performance.